(untitled) (Research, Society and Development, 2025)
Bovine tuberculosis is a zoonotic disease with economic and health implications for livestock. This study analyzed the spatiotemporal dynamics of this disease in Rondônia from 2020 to 2024, based on data from the Agency of Agrosilvopastoral Sanitary Defense of the State of Rondônia (Idaron), aiming to support control strategies. This is a descriptive-exploratory research with a retrospective analysis of official secondary data. The results revealed a significant scarcity of updated data, with public records available only for 2019 (4 cases) and 2020 (1 case), indicating low incidence but preventing a complete analysis of the trend in the target period. The distribution of cases across five different municipalities points to the geographic dispersion of the disease. It is concluded that the epidemiological trend could not be definitively established due to limited information. The central conclusion is the critical need to systematize and regularly disseminate epidemiological data, whose updating is essential to guide effective health policies, direct resources, and monitor the effectiveness of the National Program for the Control and Eradication of Animal Brucellosis and Tuberculosis (PNCEBT) in the state.